PENGARUH KONTEN MARKETING DI MEDIA SOSIAL INSTAGRAM, TESTIMONI DAN TAGLINE TERHADAP MINAT BELI DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING PADA KEDAI KAMSITU DI KECAMATAN SITUBONDO - Suhendra, Suhendra; Praja, Yudha; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
Marketing through social media is an important need for business actors today. The reason is, customers have turned to social media platforms for various purposes, from socializing to shopping. Social media offers a wide reach, making it a top choice for businesses in marketing efforts. This is further reinforced by the emergence of various marketing features provided by social media platforms, such as those offered by Instagram as a prime example. The purpose of this study is to analyze and test the influence of Marketing Content, Testimonials, Taglines on Buying Interest through Trust as an Intervening Variable. The population in this study is consumers in Kedai Kamsitu. The sampling technique uses a simple random sampling method. Data analysis and hypothesis using the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the PLS 3.0 smart application, show that marketing content has a significant positive effect on trust, testimonials have a positive but not significant effect on trust, tagline has a significant positive effect on trust, content marketing has a significant positive effect on buying interest, testimonials have a negative but not significant effect on buying interest, tagline has an effect Significant positive effect on Buying interest, Trust has a significant positive effect on Buying interest, Content marketing has a significant positive effect on Buying interest, Testimonials have a positive but not significant effect on Buying interest through Trust, Tagline has a positive but not significant effect on Buying interest through Trust.